A Framework of Single-Session Problem-Solving in Elite Sport: A Longitudinal, Multi-Study Investigation - Pitt, Tim; Thomas, Owen; Lindsay, Pete; Hanton, Sheldon; Bawden, Mark (Frontiers in Psychology, 2020)
In this six-year, multi-study paper we summarize an effective framework of single-session problem-solving developed in an elite sport context at a world leading national institute of sport science and medicine (English Institute of Sport: EIS). In Study 1, we used ethnography (3.5 years) to observe how single-session problem-solving methods were being considered, explored, introduced and developed within the EIS. In Study 2, we used case-study methods split into two parts. A multiple case-study design (10 cases) was employed in Part one to evaluate how the approach was refined into an effective framework of practice. An individual case-study is then illustrated to detail the framework in-action. Collectively, findings realized a framework of single-session problem-solving for use both inside and outside of elite sport that focused on ways to reframe clients’ problems into more ‘solvable’ descriptions. Guidance for psychologists wishing to integrate these problem-solving techniques into their practice are offered.